Capaian Indikator Kapitasi Berbasis Komitmen Pelayanan pada Puskesmas di Kota Semarang - Anton Kristijono (Jurnal Rekam Medis dan Informasi Kesehatan, 2020)
Start from 2017, the capitation payment based on the fulfilment of service commitment has been implemented throughout all FKTP in Indonesia. There are three ration indicators of service commitment: contact number (≥150 per mile), ratio of participants of Prolanis who regularly visit (≥50%), and the ratio of non-specialistic outpatient referral (≤5%). The achievement of indicator target shows the service quality and influences the amount of capitation rate obtained by the Community Health Centre from BPJS Kesehatan. The research objective is to identify the glimpse of the achievement of the three indicators and the achievement of capitation number in 37 (thirty seven) Community Health Centres in Semarang City in 2018 and Semester 1 of 2019. The research method is descriptive observational, where during the the research, there has not been any intervention implemented. The data type used is quantitative data obtained from the secondary data of BPJS Kesehatan, Department of Health of Semarang City and Community Health Centres.The research result describes the average achievement of Contact Number of semester 1 and 2 in 2018 which reached 156.43 per mile and 157.08 per mile bigger that the indicator target, semester 1 of 2019 was 144.99 per mile, under the indicator target. Prolanis ratio describes that the Prolanis participants registered in Community Health Centres in Semarang City who regularly pay a visit to the Community Health Centres to obtain the service over chronic diseases they suffer continuously. Non-specialistic outpatient referral ratio suggests that the service quality in Community Health Centres in Semarang city is good. The average achievement of capitation payment based on the service commitment of the same period respectively is: 97,74%; 98,07%; 98,07%. Community Health Centre of Karanganyar has the lowest average achievement of capitation payment in 2018 as well as in Semester 1 of 2019 of 92.50% which shows that in average, there are 2 (two) indicators of capitation payment based on service commitment in Community Health Centres of Karanganyar which is located in unsafe zone during that period.Abstrak        Mulai tahun 2017 pembayaran kapitasi berbasis pemenuhan komitmen pelayanan dilaksanakan di seluruh FKTP di Indonesia. Terdapat tiga rasio indikator komitmen pelayanan : angka kontak (≥150 per mil), rasio peserta prolanis rutin berkunjung (≥50%), dan rasio rujukan rawat jalan non spesialistik (≤5%). Pencapaian target indikator menunjukan kualitas pelayanan dan mempengaruhi besaran tarif kapitasi yang didapat Puskesmas dari BPJS Kesehatan. Tujuan penelitian untuk mengetahui gambaran pencapaian ketiga indikator dan capaian besaran kapitasi pada 37 (tigapuluh tujuh) Puskesmas di Kota Semarang tahun 2018 dan semester 1 tahun 2019. Jenis penelitian adalah observasional deskriptif, dimana selama penelitian berlangsung tidak dilakukan intervensi. Jenis data yang digunakan : data kuantitatif, yang berasal dari data sekunder BPJS Kesehatan, Dinas Kesehatan Kota Semarang.       Hasil penelitian menggambarkan rata-rata capaian Angka Kontak  semester 1 dan semester 2 tahun 2018 mencapai 156,43 per mil dan 157,08 per mil lebih besar dari target indikator, semester 1 tahun 2019 adalah 144,99 per mil, di bawah target indikator. Rata-rata capaian peserta Prolanis rutin berkunjung dan rata-rata capaian rasio rujukan rawat jalan non spesialistik pada periode yang sama, hasilnya di atas target indikator. Rata-rata capaian pembayaran kapitasi pada periode yang sama berturut-turut : 97,74%; 98,07%; 98,07%. Puskesmas Karanganyar rata-rata capaian pembayaran kapitasinya terendah selama tahun 2018 serta semester 1 tahun 2019 sebesar 92,50%.